E-Booklet on Preparation Behavior for Exclusive Breastfeeding of Pregnant Women - Prihatini, Fitri; Sulistyowati, Dina Indrati Dyah; Elisa, Elisa; Wagiyo, Wagiyo (JENDELA NURSING JOURNAL, 2024)
Background: Factors that influence mothers in providing exclusive breastfeeding are lack of exposure to information about lactation management and lack of time for working mothers to provide breast feeding directly. One effort that can be made is providing counseling and demonstrations about lactation management using e-booklets to pregnant women to improve preparation for exclusive breastfeeding.Purpose: To understand the influence of lactation management efforts on behavior in preparation providing exclusive breastfeeding to pregnant women.Methods: This research uses a quasi-experimental research design with pre-test and post-test with control group. The number of samples in this study was all primigravida pregnant women in the second and third trimesters, totaling 56 people. Sampling used total sampling technique. Data analysis used the Man-Whitney test.Results: The results of the analysis of the intervention group obtained a p-value of 0.000, so there was a significant difference in the pre-test and post-test on the behavior of pregnant women regarding lactation management in the intervention group. The results of the control group analysis obtained a p-value of 0.272 so there was no significant difference in the pre-test and post-test on the behavior of pregnant women regarding lactation management in the control group. The research results obtained a p-value of 0.005, so there was a significant difference in the average behavior of pregnant women between the intervention and control groups.Conclusion: There is an influence of lactation management efforts on improving the behavior of pregnant women in preparation for exclusive breastfeeding.